Analysis of the trend of pH changes of concrete pore solution during the hydration by various analytical methods. (June 2022) - Natkunarajah, Kapilraj; Masilamani, Koneswaran; Maheswaran, Sithambaresan; Lothenbach, Barbara; Amarasinghe, D.A.S.; Attygalle, Dinesh
Abstract: The pH is an important parameter in concrete health monitoring. Many studies have been conducted to investigate the environmental elements that influence the pH value of concrete. This study focussed on the investigation of the pore solution in concrete throughout the hydration process during a 90-day timeframe. The concrete pore solution was extracted by ex-situ leaching methods (ESL) including cold water and hot water extraction (CWE and HWE). The pH of the solutions was obtained by various techniques such as titration, direct measurement by pH electrode, back calculation method, and the thermodynamic modelling based on the measured alkali concentrations. For both ex-situ leaching processes, the changes in pH and alkali concentration appear to be similar. Due to the dilution effect of water addition, direct pH measurement with a pH electrode and titration method underestimates the real pH value. The results obtained from the measured alkali concentrations were more reliable and indicated that the pH of the fresh concrete was around 13.1 and increased gradually up to 13.8 with time. Back calculation of the pH of the concrete using the dilution of the H + ions show the high pH values. Therefore, the actual pH of the concrete pore solution can be evaluated using a thermodynamic modelling based on the alkali content of the extracted solution.